THE DEMOCRATIC DEVELOPMENT 0F NEW UZBEKISTAN AND TRANSFORMATIONS IN ETHNIC CONSCIOUSNESS - Dusmuratovich, Narkulov Sukhrob; Saidikramovna, Umarova Farida (PT. Antis International Publisher, 2024)
General Background: The article explores the political modernization of Uzbekistan during its current phase of democratic transformation. Specific Background: Under President Shavkat Mirziyoyev’s leadership, Uzbekistan has embarked on significant reforms aimed at aligning governance with democratic values and addressing ethnic consciousness. Knowledge Gap: While political modernization in post-autocratic societies is often analyzed, little focus has been given to Uzbekistan's specific context, particularly regarding its blend of Eastern evolutionary reform and Western democratic ideals. Aims: This study aims to examine Uzbekistan's approach to modernization, assessing its impact on national consciousness, ethnic identity, and democratic values. Results: Findings reveal that Uzbekistan’s approach to democratic transformation emphasizes gradual, socially attuned reform rather than abrupt change, fostering a sense of national identity that aligns with peace, cooperation, and open governance. Novelty: This research introduces a unique perspective on Uzbekistan’s modernization, merging Eastern gradualism with democratic principles, which reflects an evolving socio-political consciousness. Implications: The study provides valuable insights for understanding political transformation in post-autocratic societies, highlighting a model that prioritizes institutional reform, public accountability, and a deepening of democratic values integrated into daily life.